A Low-Valent Iron Imido Heterocubane Cluster: Reversible Electron Transfer and Catalysis of Selective C-C Couplings - Lichtenberg, Crispin; Garcia Rubio, Ines; Viciu, Liliana; Adelhardt, Mario; Meyer, Karsten; Jeschke, Gunnar; Gruetzmacher, Hansjoerg (Angewandte Chemie International Edition, 2015)
Enzymes and cofactors with iron-sulfur heterocubane core structures, [Fe4S4], are often found in nature as electron transfer reagents in fundamental catalytic transformations. An artificial heterocubane with a [Fe4N4] core is reported that can reversibly store up to four electrons at very negative potentials. The neutral [Fe4N4] and the singly reduced low-valent [Fe4N4]- heterocubanes were isolated and fully characterized. The low-valent species bears one unpaired electron, which is localized predominantly at one iron center in the electronic ground state but fluctuates with increasing temperatures. The electrons stored or released by the [Fe4N4]/[Fe4N4]- redox couple can be used in reductive or oxidative C-C couplings and even allow catalytic one-pot reactions, which show a remarkably enhanced selectivity in the presence of the [Fe4N4] heterocubanes.
CRIS-Team Scopus Importer:2020-09-14
Keywords: C-C coupling; cluster compounds; heterocubanes; homogeneous catalysis; low-valent iron